2002
DOI: 10.1002/j.1939-4640.2002.tb02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Regulation of Aquaporins 1, 8, and 9 in the Testis, Efferent Ducts, and Epididymis of Adult Rats and During Postnatal Development

HAITHAM H. BADRAN,
LOUIS S. HERMO

Abstract: Aquaporins (AQPs) are membrane protein channels that allow the rapid passage of water through an epithelium containing tight junctions. In the present study, light microscope immunocytochemistry was utilized to localize several members of the AQP family in the testis, efferent ducts, and epididymis of normal adult animals during postnatal development and after various experimental procedures on adult animals. In the testis of normal adult animals, AQP‐8 was expressed exclusively in Sertoli cells, while AQP−l9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(2 citation statements)
references
References 70 publications
1
1
0
Order By: Relevance
“…In the neonatal mouse efferent ductules, immunostaining for AQP3, AQP9 and CFTR were not observed in any treatment groups (data not shown). This is consistent with previous report that no AQP1 and AQP9 detectable by immunohistochemistry in rat efferent ductules before postnatal days 7 to 21 (Badran and Hermo 2002). It is possible that no expression of these proteins or too low to be detected by immunohistochemistry in neonatal murine efferent ductules.…”
Section: Selective Deletion Of Fgf4 In Testicular Germ Cells Results ...supporting
confidence: 93%
“…In the neonatal mouse efferent ductules, immunostaining for AQP3, AQP9 and CFTR were not observed in any treatment groups (data not shown). This is consistent with previous report that no AQP1 and AQP9 detectable by immunohistochemistry in rat efferent ductules before postnatal days 7 to 21 (Badran and Hermo 2002). It is possible that no expression of these proteins or too low to be detected by immunohistochemistry in neonatal murine efferent ductules.…”
Section: Selective Deletion Of Fgf4 In Testicular Germ Cells Results ...supporting
confidence: 93%
“…To date, locations of classical AQPs have been identified and described within both of these structures, and their presence in this region, especially in the cell membrane, is relatively high [38,[43][44][45]. The available data on the occurrence of aquaglyceroporins in this part of the reproductive system come, among other pieces of data, from a study by Badran and Hermo [46]. These authors observed the expression of AQP9 in the microvilli of the non-ciliated cells of the rat efferent ducts.…”
Section: Discussionmentioning
confidence: 99%